Overexpression of KCNJ3 gene splice variants affects vital parameters of the malignant breast cancer cell line MCF-7 in an opposing manner. Issue 1 (December 2016) - Rezania, S.; Kammerer, S.; Li, C.; Steinecker-Frohnwieser, B.; Gorischek, A.; DeVaney, T.; Verheyen, S.; Passegger, C.; Tabrizi-Wizsy, N.; Hackl, H.; Platzer, D.; Zarnani, A.; et al.
Abstract Background Overexpression theKCNJ3, a gene that encodes subunit 1 of G-protein activated inwardly rectifying K+ channel (GIRK1) in the primary tumor has been found to be associated with reduced survival times and increased lymph node metastasis in breast cancer patients. Methods In order to survey possible tumorigenic properties of GIRK1 overexpression, a range of malignant mammary epithelial cells, based on the MCF-7 cell line that permanently overexpress different splice variants of theKCNJ3 gene (GIRK1a, GIRK1c, GIRK1d and as a control, eYFP) were produced. Subsequently, selected cardinal neoplasia associated cellular parameters were assessed and compared. Results Adhesion to fibronectin coated surface as well as cell proliferation remained unaffected. Other vital parameters intimately linked to malignancy, i.e. wound healing, chemoinvasion, cellular velocities / motilities and angiogenesis were massively affected by GIRK1 overexpression. Overexpression of different GIRK1 splice variants exerted differential actions. While GIRK1a and GIRK1c overexpression reinforced the affected parameters towards malignancy, overexpression of GIRK1d resulted in the opposite. Single channel recording using the patch clamp technique revealed functional GIRK channels in the plasma membrane of MCF-7 cells albeit at very low frequency. Discussion We conclude that GIRK1d acts as a dominant negative constituent of functional GIRK complexes present in the plasma membrane of MCF-7 cells, while overexpression of GIRK1a and GIRK1c augmented their activity. The core component responsible for the cancerogenic action of GIRK1 is apparently presented by a segment comprising aminoacids 235–402, that is present exclusively in GIRK1a and GIRK1c, but not GIRK1d (positions according to GIRK1a primary structure). Conclusions The current study provides insight into the cellular and molecular consequences ofKCNJ3 overexpression in breast cancer cells and the mechanism upon clinical outcome in patients suffering from breast cancer.